2020
DOI: 10.5152/eurasianjmed.2020.20118
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned so Far from the Pandemic: A Review on Pregnants and Neonates with COVID-19

Abstract: Aims and Scope Eurasian Journal of Medicine (Eurasian J Med) is an international, scientific, open access periodical published by independent, unbiased, and tripleblinded peer-review principles. The journal is the official publication of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 58 publications
1
44
0
2
Order By: Relevance
“…Knowledge about neonatal outcomes of SARS-CoV-2 infection is relatively limited. Immaturity of both innate and adaptive immune systems make this group highly vulnerable to infection [70]. Interestingly, the majority of neonates born to mother with COVID-19 were not infected, and to date few reports have suggested that neonates have been affected by COVID-19.…”
Section: Neonatal Period and Vertical Transmissionmentioning
confidence: 99%
“…Knowledge about neonatal outcomes of SARS-CoV-2 infection is relatively limited. Immaturity of both innate and adaptive immune systems make this group highly vulnerable to infection [70]. Interestingly, the majority of neonates born to mother with COVID-19 were not infected, and to date few reports have suggested that neonates have been affected by COVID-19.…”
Section: Neonatal Period and Vertical Transmissionmentioning
confidence: 99%
“…Among the complications of pregnancy, premature rupture of the membranes, coagulopathies and liver dysfunction are reported. There is also an increased number of cesarean sections and premature deliveries [11].…”
Section: The Course Of the Disease In Pregnant Womenmentioning
confidence: 99%
“…Currently, COVID-19 disease in pregnant women is not an indication for termination of pregnancy [12]. Mild and stable cases should be monitored, and the pregnancy continued, and in critical situations, when there is a high risk to the life of the fetus and mother, termination of pregnancy should be considered [11]. A multidisciplinary team should manage cases of pregnancy in women with COVID-19.…”
Section: The Course Of the Disease In Pregnant Womenmentioning
confidence: 99%
“…Thus, essential notes obtained from these webinars have been shared with the other members 6 . Additionally, the team members prepared review articles, regarding the most relevant knowledge on COVID-19, which are in the publication process [7][8][9] . Besides, this crisis has affected face-toface meetings and the communication of members who are living in different parts of the country; an online meeting was organized among the group members after completing the final e-book, the record of the Zoom meeting is available from YouTube and it gives a reflection of the source of the group's motivation -solidarity and collaboration 10 .…”
Section: An Example Of National Scientific Collaboration During the Cmentioning
confidence: 99%